2003
DOI: 10.1021/jf0212385
|View full text |Cite
|
Sign up to set email alerts
|

Turkish Tombul Hazelnut (Corylus avellana L.). 1. Compositional Characteristics

Abstract: The quality of Tombul (Round) hazelnut, grown in the Giresun province of Turkey, was determined by measuring proximate composition, minerals, vitamins, dietary fiber, amino acids, and taste active components (free amino acids, sugars, and organic acids). Fat was the predominant component in Tombul hazelnut (approximately 61%). The major minerals were potassium, phosphorus, calcium, magnesium, and selenium. Hazelnut was also found to serve as an excellent source of vitamin E (24 mg/100 g) and a good source of w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

23
142
5
4

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 209 publications
(174 citation statements)
references
References 59 publications
23
142
5
4
Order By: Relevance
“…In contrast with a Step I or Step II diet, a MUFA diet tends to raise HDL cholesterol and lower TAG concentrations (Grundy, 1986;Mensink and Katan, 1987;Rajaram et al, 2001;Hyson et al, 2002). In keeping with this evidence, hazelnut that is an excellent source of MUFA (Alasalvar et al, 2003b, c), may help in this respect.…”
Section: Introductionmentioning
confidence: 80%
See 3 more Smart Citations
“…In contrast with a Step I or Step II diet, a MUFA diet tends to raise HDL cholesterol and lower TAG concentrations (Grundy, 1986;Mensink and Katan, 1987;Rajaram et al, 2001;Hyson et al, 2002). In keeping with this evidence, hazelnut that is an excellent source of MUFA (Alasalvar et al, 2003b, c), may help in this respect.…”
Section: Introductionmentioning
confidence: 80%
“…Hazelnut, which contains lipid-lowering constituents such as MUFA, PUFA, b-sitosterol and soluble dietary fiber (Jones et al, 1997;Brown et al, 1999;Zambó n et al, 2000;Alasalvar et al, 2003b, c), offers an opportunity as a potential hyporcholesterolemic 'heart-healthy' diet component. Incorporation of hazelnut (40 g/day) into human diet favorably altered multiple plasma lipid variables in hypercholesterolemic adult men (Figure 1 and Table 5).…”
Section: Effects Of Hazelnut-enriched Diet On Plasma Lipid Profiles Smentioning
confidence: 99%
See 2 more Smart Citations
“…Proximate composition of hazelnut is about 62 % fat, 16 % protein and 11 % carbohydrate and changes with variety. Hazelnut composition (Alasalvar et al 2003;Venkatachalam and Sathe 2006), and good antioxidant effects of hazelnut (Amaral et al 2006;Oliveira et al 2008) are reported in literature.…”
Section: Introductionmentioning
confidence: 99%